Disparities in melanoma Breslow thickness at diagnosis in north-east London - Yik Ting Chan (Clinical Medicine, 2025)
Background: International studies have observed inequalities in the stage of diagnosis of melanoma.1–5 Given that this has not been sufficiently studied in the UK, the purpose of this study was to investigate whether there are age-related, gender and ethnic disparities in the diagnosis of melanoma that could be modified with the improvement of patient awareness or GP and/or dermatologists' resources by looking at the Breslow Thickness (BT) at diagnosis in hospitals. Aims: To improve early detection and potentially improve disease-specific outcomes in patients with melanoma. Method: In this retrospective study, I obtained 483 cases of melanoma and tertiary referral cases between 2019 and 2021. An anonymised cases list was obtained from the Cancer Registry, while the epidemiology data, clinical details and histology reports, including BT of melanoma at diagnosis, were obtained from the electronic care record system (CRS). Associations between advanced melanoma (thickness >4.0 mm) and patients’ epidemiological factors, including age, ethnicity and gender, were described and analysed using graphs. Results: In total, 483 patients had histologically confirmed melanoma and thickness information. Of these, 52.8% were women, the median age at diagnosis was 61 years and 15.3% had advanced melanoma (BT >4 mm) (Table 1). The data revealed that thicker melanoma and more advanced stages of the disease were more commonly seen in older patients compared with their younger counterparts. Men were more likely to have advanced and ulcerated tumours at diagnosis. The proportion of patients from ethnic minorities presenting with more advanced melanoma varied across the different hospitals, with overall a minority of cases (18.7 %) presenting in ethnic minorities (Fig 1). For advanced cases in ethnic minorities, the majority of patients were White-non British. Interpretation: The data showed that there are age-related and gender disparities, and potential ethnic disparities, at diagnosis for patients with melanoma in the study groups. However, the statistical significance of these findings is pending further evaluation by the dermatology clinical team. Conclusion: This study provides a comprehensive description of the variation of BT of melanoma at presentation among different age groups, ethnic groups and genders. The results suggest that more emphasis is needed on the promotion of skin self-examination and enhancement of awareness in high-risk populations to improve the outcome of patients.